Corporate social responsibility and its social aspects - Hyršlová, Jaroslava; Bednaříková, Marie; Vávra, Jan (Univerzita Pardubice, 2008)
Corporate Social Responsibility (CSR) is a trend that respects the sustainable development concept and emphasizes the social aspects of sustainable development. This paper is concerned with social aspects of CSR (i.e. sustainable development) and their introduction into corporate practice. Emphasis is first placed on perception of the concept of sustainable development and its social aspects in corporate practice. The social aspects of sustainable development at the corporate level constitute a very broad topic. Consciousness of the importance of active work with human resources, leading to full utilization of their potential for the company plays an important role. Social performance composes a significant part of the corporate image and the corporate image has a significant influence on the corporate economic performance.